2012
DOI: 10.1007/s10964-012-9742-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Violent Video Gaming, Empathic Concern, and Prosocial Behavior Toward Strangers, Friends, and Family Members

Abstract: Exposure to media violence, including violent video gaming, can have a cognitive desensitization effect, lowering empathic concern for others in need. Since emerging adulthood offers increased opportunities to volunteer, strengthen relationships, and initiate new relationships, decreases in empathic concern and prosocial behavior may prove inhibitive to optimal development during this time. For these reasons, the current study investigated associations between violent video gaming, empathic responding, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 75 publications
2
48
1
1
Order By: Relevance
“…1 Direct estimates are frequently used in survey research to measure media violence exposure (e.g., Fraser et al, 2012;Nikkelen et al, 2014;Slater, 2004;Slater, Henry, Swaim, & Anderson, 2003) and has been found reliable and valid for use with adolescents samples (Fikkers, Piotrowski, & Valkenburg, 2015). Direct estimates measured exposure to violent content on television and in electronic games with two items each (four items in total): Participants were given the following definition of violence: "All violence (for example, fighting and shooting) that living beings (for example, humans and monsters) do to each other."…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Direct estimates are frequently used in survey research to measure media violence exposure (e.g., Fraser et al, 2012;Nikkelen et al, 2014;Slater, 2004;Slater, Henry, Swaim, & Anderson, 2003) and has been found reliable and valid for use with adolescents samples (Fikkers, Piotrowski, & Valkenburg, 2015). Direct estimates measured exposure to violent content on television and in electronic games with two items each (four items in total): Participants were given the following definition of violence: "All violence (for example, fighting and shooting) that living beings (for example, humans and monsters) do to each other."…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are several cross-sectional studies that have demonstrated that media violence is negatively associated with empathy (Anderson et al, 2010;Bartholow, Sestir, & Davis, 2005;Fraser et al, 2012;Funk, 2005;Funk, Baldacci, Pasold, & Baumgardner, 2004;Wei, 2007). This relationship is generally explained by one of two processes.…”
Section: The Relationship Between Media Violence Empathy and Sympathymentioning
confidence: 99%
See 3 more Smart Citations